Outline of surface mass balance at Dome Fuji, East Antarctica, by the stake method from 1995 to 2006 - Takao Kameda; Hideaki Motoyama; Shuji Fujita; Shuhei Takahashi (National Institute of Polar Research, 2008)
This paper describes observational results of surface mass balance (SMB) at Dome Fuji (77°19'01″S, 39°42'11″E; 3810m a.s.l.), East Antarctica from 1995 to 2006. The SMB was estimated using 36 bamboo stakes (grid of 6×6, placed at 20m intervals). The heights of the stake tops from the snow surface were measured at 0.5cm resolution twice monthly in 1995, 1996, 1997, and 2003, and once a year for the rest of the study period. The annual SMB from 1995 to 2006 at Dome Fuji was 27.3±1.5kgm^<-2>a^<-1>. This result agrees well with the annual SMB from AD 1260 to 1993 (26.4kgm^<-2>a^<-1>), estimated from volcanic signals in the Dome Fuji ice core. From 1995 to 2006, there were 37 incidences of negative or zero annual SMB, which was 8.6%. Compared with similar studies at Vostok, South Pole and Dome C, we found that a site with SMB over 190kgm^<-2>a^<-1> is expected to have annual snow accumulation at the 95% confidence level. Sites from 1500 to 2500m above sea level fit the criteria on the Antarctic ice sheet. According to stake and snow pit observations at Vostok, we estimated that the probability of an annual layer missing (hiatus) at Dome Fuji under present-day and glacial conditions are 9.4% and 11.4%, respectively. Variations of SMB measured by 36-stakes for 12 years were also analyzed.